205k views
5 votes
Pressions: Practice

Question 1 of 5
Select the correct answer.
Which expression is equivalent to the given expression?
3(x – 7) + 4(x2 – 2x + 9)

User Xsor
by
4.7k points

1 Answer

3 votes

Answer: 14

Step-by-step explanation: Factoring x2-2x+9

The first term is, x2 its coefficient is 1 .

The middle term is, -2x its coefficient is -2 .

The last term, "the constant", is +9

Step-1 : Multiply the coefficient of the first term by the constant 1 • 9 = 9

Step-2 : Find two factors of 9 whose sum equals the coefficient of the middle term, which is -2 .

The first term is, 4x2 its coefficient is 4 .

The middle term is, -5x its coefficient is -5 .

The last term, "the constant", is +15

Step-1 : Multiply the coefficient of the first term by the constant 4 • 15 = 60

Step-2 : Find two factors of 60 whose sum equals the coefficient of the middle term, which is -5 .

-60 + -1 = -61

-30 + -2 = -32

-20 + -3 = -23

-15 + -4 = -19

-12 + -5 = -17

-10 + -6 = -16

For tidiness, printing of 18 lines which failed to find two such factors, was suppressed

4x2 - 5x + 15= x=14

User MagicKat
by
4.8k points
Welcome to QAmmunity.org, where you can ask questions and receive answers from other members of our community.